2018
DOI: 10.22201/ib.20078706e.2018.2.2367
|View full text |Cite
|
Sign up to set email alerts
|

Track analysis of the funnel-web spiders (Araneae: Agelenidae) of Mexico

Abstract: We analyzed distributional data of 59 species of funnel-web spiders (Araneae: Agelenidae) of Mexico. We constructed individual tracks for the species analyzed, based on published and unpublished records, and based on their overlap we obtained 9 generalized tracks. Three generalized tracks belong to the Californian Nearctic dominion (Nearctic region) and 6 generalized tracks extend along the Mexican transition zone. Seven generalized tracks are defined by species of the same genus or closely related genera and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For spiders, to date, there are about 414 described species for the whole Baja California peninsula (Jiménez et al, 2018), a number certainly due to increase with further studies (Hernández-Salgado et al, 2022). Furthermore, a trackanalysis found that the Baja California peninsula hosts 3 of 9 generalized tracks for Mexico based on agelenid spiders (Maya-Morales et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For spiders, to date, there are about 414 described species for the whole Baja California peninsula (Jiménez et al, 2018), a number certainly due to increase with further studies (Hernández-Salgado et al, 2022). Furthermore, a trackanalysis found that the Baja California peninsula hosts 3 of 9 generalized tracks for Mexico based on agelenid spiders (Maya-Morales et al, 2018).…”
Section: Introductionmentioning
confidence: 99%